Cross-sectional epidemiology of hearing loss in Australian children aged 11–12 years old and 25-year secular trends - Mensah, Fiona K; Liu, Richard; Wake, Melissa; Gold, Lisa; Burt, Rachel A; Wang, Jing; le Clercq, Carlijn; Sung, Valerie; Carew, Peter (My University, 2018)
Objective In a national study of Australian children aged 11–12 years old, we examined the (1) prevalence and characteristics of hearing loss, (2) its demographic risk factors and (3) evidence for secular increases since 1990. Methods This is a cross-sectional CheckPoint wave within the Longitudinal Study of Australian Children. 1485 children (49.8% retention; 49.7% boys) underwent air-conduction audiometry. Aim 1: hearing loss (≥16 decibels hearing level (dB HL)) was defined in four ways to enable prior/future comparisons: high Fletcher Index (mean of 1, 2 and 4 kHz; primary outcome relevant to speech perception), four-frequency (1, 2, 4 and 8 kHz), lower frequency (1 and 2 kHz) and higher frequency (4 and 8 kHz); aim 2: logistic regression of hearing loss by age, gender and disadvantage index; and aim 3: P for trend examining CheckPoint and reported prevalence in studies arranged by date since 1990. Results For high Fletcher Index, the prevalence of bilateral and unilateral hearing loss ≥16 dB HL was 9.3% and 13.3%, respectively. Slight losses (16–25 dB HL) were more prevalent than mild or greater (≥26 dB HL) losses (bilateral 8.5% vs 0.8%; unilateral 12.5% vs 0.9%), and lower frequency more prevalent than higher frequency losses (bilateral 11.0% vs 6.9%; unilateral 15.4% vs 11.5%). Demographic characteristics did not convincingly predict hearing loss. Prevalence of bilateral/unilateral lower and higher frequency losses ≥16 dB HL has risen since 1990 (all P for trend <0.001). Conclusions and relevance Childhood hearing loss is prevalent and has risen since 1990. Future research should investigate the causes, course and impact of these changes.
Archives of Disease in Childhood
Keywords: Health and wellbeing; Health and wellbeing